Determining Participants in the Web Technologies Student Competency Competition Using the Vikor Method - Maulia Rahman (Journal Electrical and Computer Experiences, 2023)
The selection of participants in the student competency competition (LKS) of SMK Swasta Tritech Informatika Medan is done manually by collecting students, calculating and comparing with supporting data such as the average competency score in the report by productive teachers. In order to be more efficient and right on target in selecting students as participants in the student competency competition at SMKS Tritech Informatika Medan, the head of the department must change the system. The application of the VIKOR method is used in determining the order or priority in efficient and simple multicriteria analysis. Based on the research sample data, with the lowest Qi result score, namely value 0, selected as a participant in the Student Competency Competition (LKS) which will represent the SMK Tritech Informatika Medan school for the Software Engineering and Game Department, namely alternative A8 with the student's name Nafil Rizqtrianto with 6 criteria, namely Mastering programming languages, Understanding Framework, Understanding program analysis, Understanding OOP, Mastering databases and report card scores.